Transformasi Metodologi Pembelajaran Al-Qur’an Hadits Berbasis Gamification untuk Meningkatkan Keterlibatan Siswa Generasi Z - Suparno, Suparno; Hidayat, Rian (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to examine the effectiveness of transforming the Quran and Hadith learning methodology through a gamification approach on the engagement level of Generation Z students at senior high schools in Sarolangun Regency. This study used qualitative research methods with a case study approach. The results show that game elements such as leaderboards, badges, and challenges significantly increase students' active participation and retention of understanding of the hadith material. In conclusion, transforming Quran and Hadith learning through gamification at senior high schools in Sarolangun Regency has proven effective in increasing the engagement of Generation Z. This methodology successfully shifted students' perceptions of religious studies from a statistical to a dynamic subject. Keywords: Quran and Hadith, Gamification, Generation Z, Student Engagement, Learning Transformation